Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1021/cc700098t
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products in Parallel Chemistry––Novel 5-Lipoxygenase Inhibitors from BIOS-Based Libraries Starting from α-Santonin

Abstract: Recently, we developed a concept known as biology-oriented synthesis (BIOS), which targets the design and synthesis of small- to medium-sized compound libraries on the basis of genuine natural product templates to provide screening compounds with high biological relevance. We herein describe the parallel solution phase synthesis of two BIOS-based libraries starting from alpha-santonin (1). Modification of the sesquiterpene lactone 1 by introduction of a thiazole moiety followed by a Lewis-acid-mediated lactone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…[189] One of the first implementationso ft his methodology was demonstrated by Analyticon, who commercialized two libraries based on andrographolide and a-santonin. [193] To synthesize thesel ibraries, the corresponding natural terpenoids were transformed into polyfunctional key scaffolds 11 and 12,w hich were suitable for further heterocyclization (Scheme 9). These scaffoldsw ere used to generate compound libraries with two diversity pointst hrough subsequentH antzsch thiazoles ynthesis and amide formation.…”
Section: Compound Libraries Based On Npsmentioning
confidence: 99%
“…[189] One of the first implementationso ft his methodology was demonstrated by Analyticon, who commercialized two libraries based on andrographolide and a-santonin. [193] To synthesize thesel ibraries, the corresponding natural terpenoids were transformed into polyfunctional key scaffolds 11 and 12,w hich were suitable for further heterocyclization (Scheme 9). These scaffoldsw ere used to generate compound libraries with two diversity pointst hrough subsequentH antzsch thiazoles ynthesis and amide formation.…”
Section: Compound Libraries Based On Npsmentioning
confidence: 99%
“…Taking this further, an ability to harness further the reactivity of a readily available natural product to widen the reach of the structural diversity available is well exemplified by Schwarz's work on -santonin. 5 Here, both the natural product 1 and a readily available variant 2 (available from 1 by acid-catalysed rearrangement) provided analogues of both of these related scaffolds that were explored as inhibitors of 5-lipoxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…Examples from the Literature Among recent works, Franke et al [13] and Schwarz et al [14] at AnalytiCon Discovery identified novel inhibitors of the 5-lipoxygenase (5-LO) pathway using 2DLBVS on their in-house compound collection. The queries constituted a list of 43 chemically diverse known inhibitors compiled from published data.…”
Section: 31mentioning
confidence: 99%